2021
DOI: 10.1002/pa.2701
|View full text |Cite
|
Sign up to set email alerts
|

Do the customer relationship benefits influence expectation of continuity? Adoption of social customer relationship management to promote eco‐friendly products

Abstract: Social media and customer relationships have become ubiquitous, and every organization now depends on both to manage and meet their organizational targets. Most organizations are now finding it necessary to adopt Social Customer Relationship Management (SCRM) to improve their marketing strategies and facilitate customer expectation of continuity. In essence, there has been a public interest in using SCRM on eco‐friendly brands, and these have become inevitable for the new generation of sustainable marketing or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Therefore, competitive organizational culture directly affects organization innovation, which implies that for firms to stay innovative, they need to be more externally focused via a competitive culture (Gopalakrishnan and Zhang, 2017). Such cultural orientation keeps firms more connected to their market (Friend and Johnson, 2017;Yu et al, 2016;Ramos et al, 2016;Huertas-Valdivia et al, 2019;Izogo and Mpinganjira, 2020;Oluwajana et al, 2021). Based on the studies reviewed on management styles, we argue and thereby posit the following: H4.…”
Section: K 5210mentioning
confidence: 94%
“…Therefore, competitive organizational culture directly affects organization innovation, which implies that for firms to stay innovative, they need to be more externally focused via a competitive culture (Gopalakrishnan and Zhang, 2017). Such cultural orientation keeps firms more connected to their market (Friend and Johnson, 2017;Yu et al, 2016;Ramos et al, 2016;Huertas-Valdivia et al, 2019;Izogo and Mpinganjira, 2020;Oluwajana et al, 2021). Based on the studies reviewed on management styles, we argue and thereby posit the following: H4.…”
Section: K 5210mentioning
confidence: 94%
“…Ethical purchasing behavior refers to environmentally friendly behavior through the consumption of sustainable products that are responsive to environmental protection (Chan, 2001;Mostafa, 2007). Although limited, the literature has identified that sustainable purchasing behavior is determined by satisfaction (Dangelico et al, 2021), trust (Oluwajana et al, 2021), price quality attributes (Sharma & Foropon, 2019;Dangelico et al, 2021), and knowledge (Dangelico et al, 2021;Joshi & Rahman, 2015). Awareness (Borin et al, 2011) and attitude (Hazen et al, 2017;Papista & Dimitriadis, 2019) play a determining role in understanding purchase behavior.…”
Section: Purchase Intention and Ethical Purchasing Behaviormentioning
confidence: 99%
“…Chen and Chang [47] and Yu and Lee [48] confirmed that customer perceptions of green values have a significantly positive effect on purchase intention. Oluwajana et al [49] suggested that customers' environmental commitment has a positive and significant effect on purchasing continuity toward an eco-friendly product.…”
Section: Formulation Of Research Hypothesesmentioning
confidence: 99%